2018
DOI: 10.1186/s12913-018-2860-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of metformin+dipeptidyl peptidase-4 inhibitors compared to metformin+sulfonylureas for treatment of type 2 diabetes

Abstract: BackgroundPatients with type 2 diabetes (T2D) typically use several drug treatments during their lifetime. There is a debate about the best second-line therapy after metformin monotherapy failure due to the increasing number of available antidiabetic drugs and the lack of comparative clinical trials of secondary treatment regimens. While prior research compared the cost-effectiveness of two alternative drugs, the literature assessing T2D treatment pathways is scarce. The purpose of this study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
(43 reference statements)
1
30
0
3
Order By: Relevance
“…As RCTs are pre‐designed, the participants enrolled are followed up during a short‐term period, and medication costs are generally covered by research funding; thus, costs are rarely evaluated in RCTs. It is noteworthy that several retrospective studies, based on data from the literature search or on hospital surveys from different countries, demonstrate that metformin+DPP‐4i treatment is cost‐effective compared to metformin+SU treatment as long‐term dual therapy in T2D, including the costs associated with hypoglycaemia, weight gain and complications . We tried to calculate medication expenditure according to patient compliance in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As RCTs are pre‐designed, the participants enrolled are followed up during a short‐term period, and medication costs are generally covered by research funding; thus, costs are rarely evaluated in RCTs. It is noteworthy that several retrospective studies, based on data from the literature search or on hospital surveys from different countries, demonstrate that metformin+DPP‐4i treatment is cost‐effective compared to metformin+SU treatment as long‐term dual therapy in T2D, including the costs associated with hypoglycaemia, weight gain and complications . We tried to calculate medication expenditure according to patient compliance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As RCTs are pre-designed, the participants enrolled are followed up during a short-term period, and medication costs are generally It is noteworthy that several retrospective studies, based on data from the literature search or on hospital surveys from different countries, demonstrate that metformin+DPP-4i treatment is cost-effective compared to metformin+SU treatment as long-term dual therapy in T2D, including the costs associated with hypoglycaemia, weight gain and complications. [28][29][30][31] We tried to calculate medication expenditure according to patient compliance in our study. Total drug expenditure over 48 weeks of treatment in the saxagliptin (Onglyza) group (¥2824) was 1.6-fold that in the glimepiride (Amaryl) group (¥1772), with comparable improvement in glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…[13] A recent study found the treatment pathway with DPP-4 inhibitors as the cost-effective second-line therapy compared to sulfonylureas from the US health care payer perspective. [14] There had been no direct comparison for cost-effectiveness of teneligliptin with sulfonylureas as combination therapy with metformin in Indian T2DM patients. So, this study was undertaken to evaluate the relative cost-effectiveness of these two combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, alogliptin is available as FDCs; thus, pill burden and pharmacy dispensing fees may allow for adherence improvement and further cost savings, respectively [89]. Studies have reported that alogliptin in combination with metformin is an alternative, cost-effective treatment compared with SUs in patients with T2DM [90, 91]. In a UK study, long-term alogliptin + metformin combination treatment achieved greater estimated lifetime quality-adjusted life-year (QALY) gains compared with SU + metformin; the associated incremental cost-effectiveness ratios (ICERs) were £10,959/QALY (12.5 mg alogliptin) and £7217/QALY (25 mg alogliptin) [90].…”
Section: Benefit Evaluationmentioning
confidence: 99%